The concept of entrepreneurial opportunities: a review and directions for future research - Schlichte, Franziska; Junge, Sebastian (Management Review Quarterly, 2024)
Shane and Venkataraman’s (2000) seminal work reshaped the landscape of entrepreneurship research by introducing the concept of entrepreneurial opportunities. Their groundbreaking article sparked a wave of scholarly interest that spawned a wealth of literature and propelled entrepreneurship research forward. However, over time, a large number of studies have been published, delving into various facets and sometimes detached determinants of the concept of entrepreneurial opportunities. Now, more than two decades after the pivotal contribution of Shane and Venkataraman (2000), it is imperative to reflect on the breadth of accumulated knowledgen and identify overlooked areas within the field of entrepreneurial opportunities. This study aims to conduct a comprehensive examination of entrepreneurial opportunities and their associated underlying processes. Using a systematic literature review, we highlight key findings from previous studies and identify research gaps that provide promising directions that future research needs to address in order to further enhance this field of researc
Keywords: Entrepreneurship; Entrepreneurial opportunities; Entrepreneurial opportunity process; Systematic literature review